PENERAPAN MODEL TEACHING GAMES FOR UNDERSTANDING DALAM PERMAINAN BOLA BESAR DI SDN MUNDAKJAYA 1 (Studi Penelitian Tindakan Kelas Pada Siswa kelas V SDN MUNDAKJAYA 1) - Vinaya, - (2018)
The purpose of this study was to find out the results of the application of the Teaching Games For Understanding model specifically in improving students' understanding of playing in big ball games. This research was conducted because there were several problems in the elementary school environment where students were still focused on the teacher when the learning process and a teacher in applying game learning were fixed to the technique. This study uses a classroom action research method (PTK) which uses 2 cycles of 4 actions at Mundakjaya 1 Elementary School SDN. , 56 volleyball games, and 59 for the overall knowledge value. From the first cycle of action I students get 60 points for soccer games, 56 basketball games, 56 volleyball games, 62 overall knowledge. In the first cycle, action II obtained a score with an average of 64 for football games, 63 basketball, 62 volleyball games, the overall value of knowledge 66. From cycle II action I got a score on soccer games with an average of 68, 64 basketball game, 67 volleyball games, overall knowledge 68. In cycle II action II got 78 football games, 78 basketball games, 78 volleyball games, 82 overall knowledge scores. From these results it can be concluded that the application of teaching games for understanding models can improve students' understanding of play.